From the era of ineffective tumor vaccines to a future with effective immunotherapy - Quincy de Waard, Wolter Igor; van den Heuvel, Michel Maria (Journal of Thoracic Disease, 2016)
Immunotherapy has become an attractive therapeutic option (1). A hundred years ago Dr. William B. Coley created inspiration by his description of the anti-cancer effects of a streptococcal vaccine (2). Since then many vaccination trials were started but few succeeded. Cancer vaccines most often introduce tumor associated antigens (TAAs) that trigger the immune responses against cancer cells (3). To be effective immunotherapeutic targets the TAAs have to have three features (4). Expression of TAAs has to be in tumor tissue, but not (or very restricted) in normal tissues. They should induce T-cell immune responses. Finally they should have biologically oncogenic characteristics. Melanoma antigen A3 (MAGE A3) was thought to be an ideal candidate TAA.